2004
DOI: 10.1038/sj.npp.1300598
|View full text |Cite
|
Sign up to set email alerts
|

Increased Attributable Risk Related to a Functional μ-Opioid Receptor Gene Polymorphism in Association with Alcohol Dependence in Central Sweden

Abstract: The m-opioid receptor (MOR), through its effects on reward and stress-responsivity, modulates alcohol intake in both animal and human laboratory studies. We have previously demonstrated that the frequently occurring A118G single-nucleotide polymorphism (SNP) in exon 1 of the MORgene (OPRM1), which encodes an amino-acid substitution, is functional and receptors encoded by the variant 118G allele bind the endogenous opioid peptide b-endorphin with three-fold greater affinity than prototype receptors. Other group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
130
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 197 publications
(149 citation statements)
references
References 42 publications
(64 reference statements)
11
130
1
4
Order By: Relevance
“…Consistent with the results of our study, multiple investigations have reported an association of the 118G allele with opioid abuse [4][5][6]. However, the mu opioid receptor is involved in multiple physiological functions, thus the 118G allele could be beneficial for some processes, but adverse for others.…”
supporting
confidence: 91%
“…Consistent with the results of our study, multiple investigations have reported an association of the 118G allele with opioid abuse [4][5][6]. However, the mu opioid receptor is involved in multiple physiological functions, thus the 118G allele could be beneficial for some processes, but adverse for others.…”
supporting
confidence: 91%
“…Relative m-receptor to k-receptor blockade effects would be expected to differ in subjects with low circulating levels of endogenous m-receptor ligands, as is the case with alcoholics and their offspring (Govoni et al, 1983;Vescovi et al, 1992;del Arbol et al, 1995;Dai et al, 2005), or in subjects with low levels of m-receptor expression, as is found in subjects with low frontal DA levels (Berthele et al, 2005) owing to their catechol-O-methyltransferase genotype (Meyer-Lindenberg et al, 2005), and in subjects with the A118G polymorphism of the m-receptor (Zhang et al, 2005). This latter polymorphism has also shown a functional differentiation in the therapeutic response to NTX (Oslin et al, 2003), and has distinguished alcoholics from non-alcoholics in some populations (Bart et al, 2005). Based on this line of reasoning, we would expect to find a group difference in NTX on decision-making, however given the small sample size and large variance within groups, this study lacked sufficient statistical power to draw such a conclusion.…”
Section: Discussion Ntx Effects On Impulsive Choicementioning
confidence: 99%
“…A number of studies have reported positive association between OPRM1 functional variant A118G and OD, [27][28][29][30] cocaine dependence (CD) 31 or AD. [31][32][33][34] Moreover, three studies adopting haplotype-based approaches also demonstrated the association between OPRM1 variants and DD or AD. [35][36][37] However, a meta-analysis showed no consistent evidence of an association of the A118G polymorphism with SD.…”
Section: Introductionmentioning
confidence: 93%